2021
DOI: 10.1111/ppc.12767
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nursing students' smartphone addiction and interaction anxiety: A descriptive relation‐seeker type study

Abstract: Purpose This study aimed to investigate the relationship between nursing students' smartphone addiction and interaction anxiety. Design and Methods This descriptive relation‐seeker type study was conducted with 333 students. The Smartphone Addiction Scale‐Short Version and the Interaction Anxiousness Scale were used. Findings Of the students who participated in the study, 12% were at risk for smartphone addiction. A statistically significant correlation was determined between the scores for the two scales used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Similar to the results of the current study, many other studies have reported an increased addiction risk following increased time spent with the smartphone (Duke & Montag, 2017;Pivetta et al, 2019;Sönmez et al, 2020;Tastan et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to the results of the current study, many other studies have reported an increased addiction risk following increased time spent with the smartphone (Duke & Montag, 2017;Pivetta et al, 2019;Sönmez et al, 2020;Tastan et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The study results have shown that increased smartphone use by the students is associated with higher scores from the SAS (Table 1). Similar to the results of the current study, many other studies have reported an increased addiction risk following increased time spent with the smartphone (Duke & Montag, 2017; Pivetta et al, 2019; Sönmez et al, 2020; Tastan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…3 However, along with depression and anxiety, the purposes of internet use (using social media, watching videos, and messaging) are significantly associated with PSU in this study, as reported in the previous studies during both COVID and non-COVID periods. 18,[38][39][40] This could be due to the lack of physical relationships and contact with relatives or friends due to restrictive social distancing and also to reduce their boredom.…”
Section: Discussionmentioning
confidence: 99%